ASSESSMENT OF TOTAL PHENOLIC CONTENT (TPC), TOTAL FLAVONOID CONTENT (TFC) AND ANTIDIARRHEAL AND ANTIOXIDANT ACTIVITIES OF DIOSCOREA BULBIFERA TUBER EXTRACT - MD. ASHRAFUL ISLAM; DIPANKAR CHAKRABORTY; SREEBASH CHANDRA BHATTACHARJEE; MD. HASAN ALI; MD. FARHAD SARKER; MD. SAMRAT MOHAY MENUL ISLAM (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: This study aims to conduct a comprehensive phytochemical screening of the tuber of Dioscorea bulbifera extract, evaluate its antioxidant capacity, and assess its anti-diarrheal activity. Methods: In this research, we reported the phytochemical screening, antidiarrheal and antioxidant activity of methanol, acetone, and dichloromethane (DCM) extracts. The qualitative phytochemical assessment of the bioactive extracts of the tuber of Dioscorea bulbifera was done. Quantitative analysis of total phenolic contents (TPC) and total flavonoid contents (TFC) were also determined. The scavenging activity of D. bulbifera was determined by DPPH assay. The antidiarrheal activity was experimented by the castor oil-induced diarrhea method. Results: TPC of Acetone, Methanol & DCM extract of D. bulbifera was 537.2, 352.7, and 79.12 μgGAE/ml, respectively, and TFC of those extracts were 2.96, 1.08, and 0.35 mgQE/g, respectively. The Acetone extract of D. bulbifera (IC50 27.99 μg/ml) showed the highest antioxidant activity. Antidiarrheal properties of the three extracts were tested at 150 mg/kg, 300 mg/kg, and 600 mg/kg per body weight (bw) in mice. The methanol and DCM extracts showed an important antidiarrheal activity by curbing 69.56% and 86.95% of diarrheal faces at the doses of 600 and 300 mg/kg/bw, respectively. Conclusion: Since the current study implies that the plant extracts gave significant results for Antidiarrheal, Antioxidant, and Phytochemical analysis, the tuber of D. bulbifera may contain therapeutic potential compounds, such as flavonoids, terpenoids, alkaloids, tannins, and saponins. These results moderate more investigation for the potential discovery of new natural bioactive compounds from this medicinal plant.